2002
DOI: 10.2134/agronj2002.1094
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Quality, and Persistence of Grazing‐ and Hay‐Type Alfalfa under Three Harvest Frequencies

Abstract: ble. Kust and Smith (1961) reported that 'Vernal' alfalfa ideally would be harvested three times (at about 42-d Producers in the lower Midwest often plant grazing-type alfalfa intervals) before 1 September in Wisconsin as a compro-(Medicago sativa L.) cultivars assuming they can withstand frequent hay harvests. However, little research has examined the long-term mise among forage yield, quality, and stand persistence. effects of frequent hay harvests on grazing-type compared with hay-However, harvesting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
97
6
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 27 publications
35
97
6
2
Order By: Relevance
“…The lower mean CP content in 2008 could be due to slightly more mature plants at harvesting time than those in the 2009. CP concentration values determined in the present study are lower than those reported by Kallenbach et al, (2002);Spandl and Hesterman (1997);and Al-Ghumaiz (2012), while they were similar with those reported by Canbolat et al (2006);and Avci et al (2007); and Karayilanli and Ayhan (2016).…”
Section: Crude Protein Contentsupporting
confidence: 90%
“…The lower mean CP content in 2008 could be due to slightly more mature plants at harvesting time than those in the 2009. CP concentration values determined in the present study are lower than those reported by Kallenbach et al, (2002);Spandl and Hesterman (1997);and Al-Ghumaiz (2012), while they were similar with those reported by Canbolat et al (2006);and Avci et al (2007); and Karayilanli and Ayhan (2016).…”
Section: Crude Protein Contentsupporting
confidence: 90%
“…Previous research has also concluded that as the interval between harvests increased, annual DM forage accumulation increased (Brink and Marten, 1989;Kallenbach et al, 2002;Putnam et al, 2005;Probst and Smith, 2011;Min, 2016). In Missouri, Kallenbach et al (2002) reported that alfalfa harvested four times per year produced 7 and 28% more than when harvested five or six times per year, respectively.…”
Section: Cutting Treatment Responsementioning
confidence: 94%
“…In Missouri, Kallenbach et al (2002) reported that alfalfa harvested four times per year produced 7 and 28% more than when harvested five or six times per year, respectively. Similarly, Min (2016) reported increasing alfalfa forage accumulation as cutting intervals increased from 28 to 42 d in Kansas.…”
Section: Cutting Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…On average over the cuttings in 2014, planting alfalfa with annual ryegrass had significantly lower crude protein contents, higher acid detergent fiber and neutral detergent fiber contents than other cover crop treatments. Nutritive values of alfalfa are generally affected by stage of maturity, cutting frequency, and harvest management (Brink and Marten, 1989;Brink et al, 2010;Kallenbach et al, 2002;Kust and Smith, 1961;Moyer et al, 1999) but nutritive values of alfalfa were also affected by cover crop tested in this study. It's not certain why alfalfa planted with annual ryegrass had the lowest nutritive values as compared to other cover crop treatments.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 66%